The Effect of Self-Control on the Construction of Risk Perceptions - Jia, Jayson S.; Khan, Uzma; Litt, Ab (Management Science, 2015)
We show that the way decision makers construct risk perceptions is systematically influenced by their level of self-control: low self-control results in greater weighting of probability and reduced weighting of consequences of negative outcomes in formulating overall threat perceptions. Seven studies demonstrate such distorted risk construction in wide-ranging risk domains. The effects hold for both chronic and manipulated levels of perceived self-control and are observed only for risks involving high personal agency (e.g., overeating, smoking, drinking). As an important implication of our results, we also demonstrate that those lower (higher) in self-control show relatively less (more) interest in products and lifestyle changes reducing consequences (e.g., a pill that heals liver damage from drinking) than those reducing likelihood of risks (e.g., a pill that prevents liver damage from drinking). We also explore several possible underlying processes for the observed effect and discuss the theoretical and managerial relevance of our findings. This paper was accepted by Yuval Rottenstreich, judgment and decision making.